Régulation internationale des dessins et modèles industriels: L'accord sur les ADPIC à l'aune du droit de l'Union européenne - Adèle Sicot (South Centre, 2024)
– This paper analyzes the provisions of the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS Agreement) on designs, and the manner in which the narrow aspects dealt with by the Agreement have been addressed by European Union (EU) legislation. The paper highlights the absence of a definition of protectable subject matter, and the considerable flexibility left to the member countries of the World Trade Organization to determine the framework of protection, notably on the basis of copyright. The paper also notes certain areas in which European legislation is more elaborate, and others which could be considered incompatible with the TRIPS Agreement.
Keywords: 300; Copyright; European Union (EU); Industrial Designs; Intellectual Property; TRIPS; TRIPS Agreement; TRIPS Flexibilities; World Trade Organization (WTO)